Nausea in pregnancy: attitudes among pregnant women and general practitioners on treatment and pregnancy care. (2nd January 2016) - Heitmann, Kristine; Svendsen, Hans Christian; Sporsheim, Ingvild H.; Holst, Lone
Abstract: Objective: Nausea and vomiting during pregnancy (NVP) is very common, and may have great impact on a woman's life. The aim of this study was to explore thoughts and attitudes among Norwegian pregnant women and GPs on treatment of NVP and pregnancy care.Design: Focus-group study.Setting and subjects: Separate focus-group discussions were conducted with pregnant women and GPs.Results: Two focus-group discussions were conducted with pregnant women and two with GPs. The GPs thought it was important to normalize NVP symptoms. However, the women felt their distress due to NVP was trivialized by the GPs. The women were sceptical towards the use of medicines while pregnant, and avoidance was sought despite being ill. The GPs appeared uncertain with respect to medical treatment of NVP, which was stated to be considered only after progression to quite severe symptoms. Sick leave seemed to be an important part of the treatment regime applied by the GPs. The women had good experiences with graded sick leave.Conclusion: This Norwegian study identifies attitudes among GPs and pregnant women that may act as obstacles to appropriate care for women with NVP. The pregnant women and the GPs seemed to talk at cross-purposes; GPs' normalization of the symptoms made the women feel that their distress due to NVP was trivialized by the GPs. Our results indicate that pregnant women with NVP requiring medical treatment probably need comprehensive and reassuring information about treatment options before considering using any medicines. Key points: Nausea and vomiting during pregnancy (NVP) is very common, and considered to be of clinical significance for 35% of women. While the GPs agreed on the importance of normalizing the symptoms, the women felt their distress was trivialized, and missed being properly evaluated. Both the GPs and the women showed a reluctant attitude to medical treatment of NVP. The GPs gave the impression of considering medical treatment only after progression of symptoms to becoming quite severe.